1998
DOI: 10.5144/0256-4947.1998.15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Malaria in the Asir Region, Saudi Arabia

Abstract: Three hundred and thirty-four eases of confirmed malaria seen in the Asir Central Hospital, Abha, in southwestern Saudi Arabia, were studied retrospectively. Two hundred and eighty-two of these (84.4%) were Saudis and the majority (72.2%) were living in the lowlands of Tihama. Transmission was found to occur throughout the year, with peaks following the rainy season and in the summer. In Saudis, falciparum malaria is more common than vivax (97.2% vs. 2.8%), while vivax malaria is more commonly seen in expatria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 1 publication
2
17
1
Order By: Relevance
“…Much higher rate of splenomegaly was recorded in P. falciparum malaria (71%) from Bikaner (Kochar et al 2006). In P. falciparum infection, splenomegaly reported from Jazan and Asir region of Saudi Arabia was 39 and 45% (Malik et al 1998, Banzal et al 1999, less than what we reported from India and Saudi Arabia. In contrast to this very low rate of splenomegaly ranging from 6.5 to 13% was reported from malaria patients of Saudi Arabia, Columbia and Thailand (Bashawri et al 2001, Echeveri et al 2003, Tangpukdee et al 2006.…”
Section: ) Is Very Close To the Values Observed In Our Studiescontrasting
confidence: 51%
“…Much higher rate of splenomegaly was recorded in P. falciparum malaria (71%) from Bikaner (Kochar et al 2006). In P. falciparum infection, splenomegaly reported from Jazan and Asir region of Saudi Arabia was 39 and 45% (Malik et al 1998, Banzal et al 1999, less than what we reported from India and Saudi Arabia. In contrast to this very low rate of splenomegaly ranging from 6.5 to 13% was reported from malaria patients of Saudi Arabia, Columbia and Thailand (Bashawri et al 2001, Echeveri et al 2003, Tangpukdee et al 2006.…”
Section: ) Is Very Close To the Values Observed In Our Studiescontrasting
confidence: 51%
“…A frequency of this symptom in 48% of individuals was reported in Saudi Arabia 19 , while in Gambia 24 it was 67%. In these two studies carried out in children under five years old, the presence of vomiting was the second most common symptom.…”
Section: Discussionmentioning
confidence: 95%
“…Some authors have made occasional reports of abdominal and osteomuscular pain, vomiting, diarrhea, hepatomegaly and splenomegaly 19,33 . Symptoms and clinical signs of the infection caused by P. vivax resemble infection caused by other species 13,33 and none of the symptoms can predict a diagnosis of malaria or differentiate the infecting species, as it has been proposed in cases of infection in children in low endemic areas 18 .…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] In Saudi Arabia, malaria transmission is confined to southwestern regions (the Aseer and Jazan provinces), where P. falciparum is the prevailing species and Anopheles arabiensis is the main vector. [7][8][9][10][11] However, malaria cases are still reported in different parts of the country, mostly brought by travelers from endemic sites in the south or expatriates from outside the country. 1,12 Chloroquine was the drug of choice for the treatment of uncomplicated malaria cases for many years.…”
Section: Introductionmentioning
confidence: 99%